Analysis of Regional Leading Sector Through Location Quotient Approach, Shift Share Analysis, and Klassen Typology (Case Study: Sanggau Regency, West Kalimantan Province) - Harjanti, Diah Trismi; Apriliyana, Muhammad Iqbal; Arini, Audi Cindra (Indonesia University of Education, 2021)
Development of economic is a must for a region, even though the region is classified as prosperous and prosperous. However, level of affluence and affluence must be increased, at least be guarded, based on this basis economic development is still needed. To optimize the direction of economic development, it’s necessary to know the potential sectors in Sanggau Regency, so its can generate significant economic growth. This research had purpose to describe the pattern of changes in economic growth and determine the potential sectors in Sanggau Regency, so the results can be taken into consideration in policy formulation and future development planning in Sanggau Regency. The method that was used in this research is descriptive with a quantitative approach. With analysis data technique uses 3 approaches is the Location Quotient (LQ) Analysis Method, Shift Share (SSA) and Klassen Typology. Sectors in Sanggau Regency which are classified as regional superior sectors include Agriculture, Forestry and Fisheries, Mining and Quarrying, and Processing Industries. Therefore, it’s hoped that the regional development strategy will prioritize the leading sectors in the area.